Modelling the influence of healthcare facilities management service quality on patients satisfaction. Issue 3 (1st July 2019) - Amankwah, Oti; Choong, Weng-Wai; Mohammed, Abdul Hakim
Abstract : Purpose: Facilities management (FM) professionals state that adopting FM will positively support core service delivery and ensure customer satisfaction. Evidences of such claim are important as it will enhance the rationale for institutionalising prudent FM service quality in hospitals in Ghana. This paper aims to assess the mediating effect of healthcare FM service quality on patients' satisfaction and overall healthcare delivery. Design/methodology/approach: This is a cross-sectional study involving adult patients at the Physician outpatient departments and Polyclinics of Komfo Anokye, Tamale and Cape Coast Teaching hospitals in Ghana. A questionnaire survey using a well-structured five-point likert scale based on the SERVQUAL dimensions and Healthcare core service dimensions rooted in the FM framework was used to collect data from 660 patients. Smart PLS was used to analyse the data of 622 valid questionnaires. Findings: The study results revealed that FM service quality mediates the relationship between patients' satisfaction and three of the constructs under core healthcare delivery. That is, (the quality of healthcare delivery, the quality of healthcare personnel and the adequacy of healthcare resources) – surprisingly, the fourth construct (the quality of administration process) was not supported. Originality/value: There is no or at best very limited studies on the contribution of healthcare FM on patients satisfaction of core healthcare delivery in Ghana. Therefore, this study will enrich and contribute to knowledge in healthcare FM in general and that of a developing African country in particular.